2018
DOI: 10.1016/j.androl.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term patient-reported satisfaction with different inflatable penile prosthesis: Comparison between AMS 700CX and Coloplast Titan

Abstract: Introduction: Erectile dysfunction (ED) is one of the most prevalent male sexual disorders worldwide. When conservative treatment is unsuccessful, contraindicated or causes unacceptable side effects penile prosthesis implantation is a definitive option for the management of ED. Although considered a third-line therapy, it achieves the highest satisfaction rates as compared with non-surgical treatment. Three-piece inflatable penile prothesis (IPP) represents the most sophisticated implantable device, AMS 700CX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…They assessed 55 patients who received either one of the prostheses using the EDITS questionnaire. The study found that there was no difference in satisfaction between patients with Titan® and patients with AMS 700 TM CX [18].…”
Section: Patient and Partner Satisfactionmentioning
confidence: 86%
See 1 more Smart Citation
“…They assessed 55 patients who received either one of the prostheses using the EDITS questionnaire. The study found that there was no difference in satisfaction between patients with Titan® and patients with AMS 700 TM CX [18].…”
Section: Patient and Partner Satisfactionmentioning
confidence: 86%
“…No patient with the Titan took longer than 6 months to optimal management. Morgado et al [18] No difference in satisfaction between patients with Titan and patients with AMS 700 CX.…”
Section: Patient and Partner Satisfactionmentioning
confidence: 95%
“…Our research clearly shows that when the highest bilateral and lowest bilateral PSV are considered, the lowest bilateral PSV clearly has a higher correlation with the clinical efficacy, penile rigidity and patient-reported treatment satisfaction (Table 5) When assessing the same variables as predictors of improvement, cure and satisfaction, the lowest PSV shows a fair-to-good ability to predict all three events, while RI on any of the four combinations was a fair predictor of cure and satisfaction, although it was a poor predictor of improvement ( Area under the receiver operating characteristic curve (AUC) are displayed. However, our group has used the same translation in two previous research articles with success (Morgado, Cavadas, Pacheco Figueiredo, & Tomada, 2018;. Clinical improvement was defined as an increase of 4 points in IIEF-5 score between baseline and last valid follow-up visit, and cure was defined as an IIEF-5 higher than 21 points at last valid follow-up visit.…”
Section: Discussionmentioning
confidence: 99%
“…There is no validated translation of the EDITS questionnaire. However, our group has used the same translation in two previous research articles with success (Morgado, Cavadas, Pacheco Figueiredo, & Tomada, 2018;. On the other hand, it is the first research article to correlate patient-reported treatment satisfaction on sildenafil citrate with penile haemodynamics and the first to address the clinical utility and implications of bilateral cavernosal artery recording.…”
Section: Discussionmentioning
confidence: 99%
“…In another study comparing the CX700 with the Titan prosthesis, there was no difference in EDITS score with a mean follow-up time of 58 months (n = 55). 80…”
Section: Patient and Partner Satisfactionmentioning
confidence: 99%